An Evaluation of UAS Pilot Workload and Acceptability Ratings with Four Simulated Radar Declaration Ranges. (December 2020) - Keeler, Jillian N.; Conrad Rorie, R.; Monk, Kevin J.; Sadler, Garrett G.; Smith, Casey
Currently, minimum operational performance standards (MOPS) are being developed for a broader rangeof unmanned aircraft system (UAS) platforms, including smaller UAS that will feature onboard sensors that are low in size, weight, and power, otherwise known as low SWaP. The low SWaP sensors used to detect non-cooperative traffic will have limited declaration ranges compared to those designed for medium-to-large UAS. A human-in-the-loop (HITL) study was conducted examining four possible radar declaration ranges (i.e., 1.5 NM, 2 NM, 2.5 NM, and 3 NM) for a potential low SWaP sensor with a detect and avoid (DAA) system encountering various non-cooperative encounters in Oakland Center airspace. Participants had lower workload, particularly workload associated with temporal demand and effort, in scenarios that featured larger detection ranges. Furthermore, participants reported better ability to remain DAA well clear within the larger declaration range conditions, specifically with the 2.5 NM and 3 NM conditions.